The COSMO-Spain Survey: Three First Rounds of the WHO Behavioral Insights Tool - Rodríguez-Blázquez, Carmen; Romay-Barja, María; Falcón, María; Ayala, Alba; Forjaz, Maria João (Frontiers in Public Health, 2021)
Objective: to describe changes in knowledge, attitudes and preventive practices (KAP), risk perception and psychological variables of Spanish population towards the COVID-19 pandemic from July to November 2020. Methods: Three samples, each of one composed by 1000+ persons aged 18 years or older, were interviewed online in three rounds, every two months, from July to November 2020. Results: The level of knowledge on COVID-19 was high in the three rounds, with percentages above 95% of correct answers related to ways of contagion and correct use of face masks. The most accepted measure was the mandatory use of face masks (80-86% of agreement in the three rounds, p=0.001), followed by the night curfew (63% of agreement). Most participants (>80%) consistently reported using face masks, ventilating spaces, and washing or disinfecting hands. However, risk perception and self-efficacy were low. Worry about losing a loved one, the health system overload and people who do not wear face masks was high (>85% of the samples). The percentage of respondents who felt depressed due to COVID-19 increased from round 1 to round 3 (p=0.044). Conclusions: Spanish population has a high degree of KAP, but a relatively low risk perception and self-efficacy. These findings can help health authorities to guide containment measures and campaigns addressed to improve preventive practices.